Characterization and Determination of Ethylene Responsive Sensor Genes in Khao Dok Mali 105 (KDML105) Rice During Rice Tungro Bacilliform Virus (Chainat isolate) (RTBVCN) Infection - Yada Mukjang; Parichart Burns (Agriculture and Natural Resources, 2006)
Ethylene receptor family including ethylene responsive sensor 1 (Os-ERS1) and ethylene responsive sensor2 (Os-ERS2) were isolated and characterized. Sequence analysis showed that both sequences of Os-ERS1 and Os-ERS2 genes comparing with japonica variety had 99.4 and 98.2 percent identity, respectively. Southern analysis indicated that only one copy of both Os-ERS1 and Os-ERS2 was found in KDML105 rice genome which located on chromosome 3 and 5, respectively. In order to understand signaling system of ethylene in rice plant during Rice Tungro Bacilliform Virus Chainat isolate (RTBVCN) infection, RTBVCN infectious clone was Agrobacterium infiltrated into the meristem of two week old rice plant. Northern analysis was performed to determine the expression of three ethylene receptors (Os-ERS1, Os-ERS2 and Os-ETR1) and four ethylene responsive factors (Os-ERFG1, Os-ERFG2, Os-ERFG3 and Os-ERFG4). The result revealed that the expression of Os-ERS1 and Os-ETR2 are elevated by RTBVCN inoculation, whereas Os-ERS2 is constitutively expressed. In transcriptional regulation step, the expression level of Os-ERFG1 is strongly induced during RTBVCN infection. Os-ERFG1 has been showed to play a major role in plant-pathogen interaction resulting in plant resistance. The result suggests the possible association of ethylene signaling in response to RTBVCN infection.